Development of an open-source software package for watershed modeling with the Hydrological Simulation Program in Fortran. (June 2015) - Lampert, D.J.; Wu, M.
Abstract: The Hydrological Simulation Program in Fortran (HSPF) is used extensively for the assessment of water quantity and water quality issues. Herein, the development of an open-source, cross-platform package for building input files, performing simulations, postprocessing and calibrating HSPF models using the Python Programming Language is presented. The flexible nature of Python opens the door to automated preprocessing and calibration routines, visualization, multiprocessing, and larger-scale model development. The software is applied using Python scripts, which provides a flexible mechanism for learning and applying HSPF. An example application of the software was used to build a calibrated HSPF model the Hunting Creek watershed within the Patuxent River Basin, Maryland, USA, which is the example application distributed with the HSPF calibration software package HSPExp. A script of a few hundred lines was used to build a calibrated model comparable to HSPExp in a simulation time of less than two hours. Highlights: Developed an operating system-independent interface to the subroutines for the Hydrological Simulation Program in Fortran (HSPF) in the Python Programming Language. Developed an open-source suite of software tools for gathering data and building input files for HSPF using Python scripting. Demonstrated the application of the software tools for automatically building a baseline HSPF model using publically-available data on the World Wide Web. Demonstrated automatic calibration using a parallel processing routine that performed favorably compared to existing software.